Indicators of urban community resilience in Putrajaya, Malaysia - Norhidayah Mohamad,; Hamzah Jusoh,; Habibah Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study examines the resilience level of the urban community in Precinct 18, Putrajaya, Malaysia. The low level of social participation among neighbourhood in Putrajaya reflects the reality of the urban community who are not ready to adapt the pressures challenges and changes of global trends. Adapting the resilience concept into community development viewed able to build a resilient community to these modern challenges. A total of 225 respondents living in Precinct 18, Putrajaya participated in this study. This study is based on survey research and the data collection was conducted by using a questionnaire. The assessment of the current level of urban community resilience is based on the localized and comprehensive indicators that have been built. Based on the mean analysis conducted, the level of resilience of the urban community in Precinct 18, Putrajaya was moderate and had a mean score (m=2.64, s.d=0.630). This study also shows the urban community resilience level is based on the localized indicators which comprise indicators from economic, social and environmental. The findings of this study are intended to guide the planning and development of the concept of community resilience as well as being the latest benchmark to the urban community resilience in the well-planned city of Putrajaya, Malaysia.